The Influence of Rewards and Punishments on the Performance of Employees : JEL Classification: M31, D12, L66, Z12, C83 - Afrilia Safitri; Ahmad Syarief Iskandar; Adzan Noor Bakri (Newinera Publisher, 2026)
The beauty and skincare industry in Indonesia has experienced significant growth, driven by increasing public awareness of self-care and the expansion of digital technology and e-commerce. Social media platforms have enabled marketing influencers to play an important role in shaping consumer perceptions and purchasing behavior. In addition, lifestyle changes and the growing attention to halal product assurance have become relevant factors influencing consumer decisions in selecting skincare products. This study aims to examine the influence of marketing influencers and lifestyle on skincare purchasing decisions, as well as the moderating role of halal awareness among consumers in Palopo City, South Sulawesi. The research employed a quantitative associative approach with data collected through questionnaires distributed to 200 skincare users. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results indicate that marketing influencers have a positive and significant effect on purchasing decisions, showing that influencer credibility, experience, and product reviews can effectively encourage consumers to purchase skincare products. Lifestyle also has a significant influence on purchasing decisions, reflecting how modern consumer lifestyles shape beauty consumption patterns. Furthermore, halal awareness moderates the relationship between lifestyle and purchasing decisions, although its moderating effect on the relationship between marketing influencers and purchasing decisions is not significant. These findings highlight the importance of influencer marketing strategies and lifestyle factors in shaping consumer behavior in the skincare market.